Comparative Effects of Proteinase Inhibitors, Plasminogen Antiactivators, Heparin and Acetylsalicylic Acid on the Experimental Disseminated Intravascular Coagulation Induced by Thrombin - Moriau, M; Rodhain, J; Noel, H; De Beys-Col, C; Masure, R (Thrombosis and Haemostasis, 1974)
In an experimental study in the rabbit, the modifications of some haemostasis parameters (platelet count, platelet retention and aggregation, platelet factors 3 and 4, platelet and plasma plasmin inhibiting activities, fibrinogen and other plasma factor levels, FDP), and histological findings are compared in both the normal animal and the animal with disseminated intravascular coagulation (DIC) induced by thrombin perfusion after administration of fibrinolytic inhibitors (plasminogen antiactivators and proteinase inhibitors).In the normal animal, the administration of fibrinolytic inhibitors is followed by haemostatic changes similar to those found in thrombophilic states. The modifications are more pronounced with plasminogen antiactivators than with proteinase inhibitors.In the animal with DIC, the administration of fibrinolytic inhibitors enhances the haemostatic and the biological disorders produced by thrombin perfusion. The effect of the plasminogen antiactivators is even more evident.The preventive administration of heparin reduces or abolishes the biological and histological disorders induced by thrombin; its beneficial effect is considerably reduced when thrombin is combined with fibrinolytic inhibitors.The administration of acetylsalicylic acid appears to be ineffective for the prevention of haemostatic and histological changes induced by thrombin perfusion.